A Case Report of Successful Conservative Treatment for Huge Acute Traumatic Intracerebral Hematoma. Issue 15 (April 2015) - Guo, Zhenyu; Sun, Lu; Dong, Quan; Liu, Chongxiao; Zhou, Ren; Gong, Shouping; Wang, Gang; Astete., Carlos Antonio Guillen
<x xml:space="preserve">Abstract</x> Abstract Acute traumatic intracerebral hematoma (ICH) is a common intracranial injury after trauma. Surgery is preferred if the volume of supratentorial hematoma is >30 mL and complicated with disturbance of consciousness or other neurofunction impairment. When supratentorial hematoma is >50 mL, patients can rarely survive if only treated with medicine. Here we present a successful case of conservative treatment for an elderly female patient with acute traumatic ICH of about 80 mL. The patient was admitted to the emergency department, with a complaint of conscious disturbance for half a month after occipital injury. A diagnosis of left prefrontal lobe cerebral contusion complicated with ICH was made after computed tomography (CT) scan. She was then treated with mannitol and dexamethasone, which were reduced stepwise for 65 and 15 days in total, respectively. The hematoma and the surrounding edema have been gradually absorbed. Eventually, she was transferred to the local hospital for rehabilitation. This report may provide additional experience on the conservative treatment for elderly patients with large ICH, which, however, needs to be evaluated carefully in different clinical settings. In addition, the younger patients in better clinical condition are still suggested to receive operation.